Entity Categorization over Large Document Collections - Ganti, Venky; König, Arnd Christian; Vernica, Rares (14th ACM International Conference on Knowledge Discovery and Data Mining (SIGKDD 2008), 2008)
Extracting entities (such as people, movies) from documents and identifying the categories (such as painter, writer) they belong to enable structured querying and data analysis over unstructured document collections. In this paper, we focus on the problem of categorizing extracted entities. Most prior approaches developed for this task only analyzed the local document context within which entities occur. In this paper, we significantly improve the accuracy of entity categorization by (i) considering an entity’s context across multiple documents containing it, and (ii) exploiting existing large lists of related entities (e.g., lists of actors, directors, books). These approaches introduce computational challenges ecause (a) the context of entities has to be aggregated across several documents and (b) the lists of related entities may be very large. We develop techniques to address these challenges. We present a thorough experimental study on real data sets that demonstrates the increase in accuracy and the scalability of our approaches.